2021
DOI: 10.20473/ijtid.v9i2.24202
|View full text |Cite
|
Sign up to set email alerts
|

Soil-Transmitted Helminthes Infection and Nutritional Status of Elementary School Children in Sorong District, West Papua, Indonesi

Abstract: It is known that soil-transmitted helminths (STHs) infection in children associates with growth and developed restriction in children, which is shown by nutritional status. However, the studies which are investigating this phenomenon is still limited in Indonesia. This recent study aimed to compare students who infected and non-infected with STH towards their nutritional status. An analytic cross-sectional research design was conducted in two elementary school students at Mayamuk sub-district, Sorong district,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Trichuris trichiura infection was most commonly observed in school-aged children at this location. A study conducted by Salma et al (30) revealed that 16.5% of schoolaged children in Mayamuk Subdistrict, Sorong Regency, were infected with one or more types of STH, including Ascaris lumbricoides, Trichuris trichiura, hookworms, and Strongyloides stercoralis. Trichuris trichiura infection was the most prevalent both in single and multiple infections.…”
Section: Resultsmentioning
confidence: 99%
“…Trichuris trichiura infection was most commonly observed in school-aged children at this location. A study conducted by Salma et al (30) revealed that 16.5% of schoolaged children in Mayamuk Subdistrict, Sorong Regency, were infected with one or more types of STH, including Ascaris lumbricoides, Trichuris trichiura, hookworms, and Strongyloides stercoralis. Trichuris trichiura infection was the most prevalent both in single and multiple infections.…”
Section: Resultsmentioning
confidence: 99%